2017
DOI: 10.1371/journal.pone.0185736
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer cell-derived fibroblast growth factors enhance osteoclast activity and contribute to the formation of metastatic lesions

Abstract: Fibroblast growth factors (FGFs) and their receptors (FGFRs) have been implicated in promoting breast cancer growth and progression. While the autocrine effects of FGFR activation in tumor cells have been extensively studied, little is known about the effects of tumor cell-derived FGFs on cells in the microenvironment. Because FGF signaling has been implicated in the regulation of bone formation and osteoclast differentiation, we hypothesized that tumor cell-derived FGFs are capable of modulating osteoclast fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 42 publications
4
22
0
Order By: Relevance
“…Similar findings were also reported by Aukes et al, who did not observe a decrease in tumor growth by bioluminescence imaging with the FGFR inhibitor BGJ398, but observed an increased bone volume in a model where breast cancer cells were injected into the femur [10]. They also showed that the treatment had no effect on sham-operated bones [10]. In our study, we observed lower serum TRACP5b levels in dovitinib-treated mice indicating that the systemic number of osteoclasts was decreased.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar findings were also reported by Aukes et al, who did not observe a decrease in tumor growth by bioluminescence imaging with the FGFR inhibitor BGJ398, but observed an increased bone volume in a model where breast cancer cells were injected into the femur [10]. They also showed that the treatment had no effect on sham-operated bones [10]. In our study, we observed lower serum TRACP5b levels in dovitinib-treated mice indicating that the systemic number of osteoclasts was decreased.…”
Section: Discussionsupporting
confidence: 92%
“…Lee et al showed that dovitinib enhances osteoblast differentiation in vitro by increasing the expression of osteoblast target genes [14]. The results by Aukes et al suggest that FGFR inhibitor BGJ398 alone has no effect on resorption activity of osteoclasts in vivo [10].…”
Section: Introductionmentioning
confidence: 99%
“…In a murine model of melanoma metastasis, it was found that for malignant tumors with RANK expression, RANKL produced by osteoblasts and bone marrow stromal cells could act as a chemical attractant and promote the migration and metastasis of malignant tumors to these sites ( 132 ). Similar effects were also found in malignant tumors such as breast cancer ( 97 , 133 135 ), prostate cancer ( 136 138 ), and lung cancer ( 100 , 104 , 139 ). The activation of phospholipase C (PLC), protein kinase C (PKC), ERK, and phosphatidylinositol-3-OH kinase (PI(3)K) pathways were involved in RANK-induced tumor cell migration ( 140 143 ).…”
Section: Rank/rankl As Regulators Of Metastasissupporting
confidence: 66%
“…In a similar context, Aukes et al . demonstrated that the supernatant of MDA-MB-231-derived bone metastasis clones induced osteoclastogenesis 25 . Unlike our approach, they used the cell culture media as a source for tumour-derived FGF and evaluated the effect of FGFR TKI on osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%